2005
DOI: 10.1111/j.1464-0597.2005.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of Children and Family Change: A Three‐Decade Portrait From Turkey

Abstract: L'étude turque sur la valeur conférée aux enfants a porté sur trois générations relevant de trois niveaux socio-économiques dans centre métropolitain et deux zones rurales. Les résultats ont montré qu'il y avait sur les trois derrières décennies un net accroissement des valeurs psychologiques attribuées aux enfants et une chute correspondante des valeurs utilitaires et économiques. La préférence pour le fils a été remplacée par la préférence pour la fille, ce qui traduit un changement de la dynamique et des rô… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
195
1
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(215 citation statements)
references
References 14 publications
5
195
1
14
Order By: Relevance
“…Although family behavior in non-Western societies has also changed over the past decades (Kagitcibasi and Ataca 2005), previous work has indicated that there are still strict norms and values on the timing and sequencing of family transitions in these societies (Koc 2007;Nauck 2002). In the typical patrilineal Turkish and Moroccan societies, the behavior of women especially is bound by rules as they may put the family's reputation at risk through disapproved actions (Bowen and Early 1993).…”
Section: Destandardization Of the Life Coursementioning
confidence: 99%
“…Although family behavior in non-Western societies has also changed over the past decades (Kagitcibasi and Ataca 2005), previous work has indicated that there are still strict norms and values on the timing and sequencing of family transitions in these societies (Koc 2007;Nauck 2002). In the typical patrilineal Turkish and Moroccan societies, the behavior of women especially is bound by rules as they may put the family's reputation at risk through disapproved actions (Bowen and Early 1993).…”
Section: Destandardization Of the Life Coursementioning
confidence: 99%
“…having someone to continue the family name). Studying 28 years of Turkish history, Kagitcibasi & Ataca [104] found that as socio-economic development increases across time or place, there is less utilitarian/economic value attributed to children and a stronger emphasis on emotional benefits, with a concomitant change in sex preference from boys to girls. Moreover, a survey of adolescents from 12 high and middle income countries showed a decline in the utilitarian value of children with economic development [105].…”
Section: (F ) Value Of Childrenmentioning
confidence: 99%
“…Publications in this vein included Turkey (Klaus 2008;Kagitcibasi and Ataca 2005), Israel and Palestine (Suckow 2005;, Indonesia (Rudolf 2010), Germany (Klaus, Nauck, and Klein 2005), the Czech Republic (Mares and Mozny 2005), South Korea (Kim and Park 2005), and China (Zheng, Shi, and Tang 2005).…”
Section: Empirical Evidence New Developments and Desideratamentioning
confidence: 99%